Expanded Newborn Screening: A Chess Board Motif in Public Health - Polizzi, Agata; Carbone, Pietro; Taruscio, Domenica (Journal of Pediatric Biochemistry, 2016)
Inborn errors of metabolism (IEM) include a large number of genetic disorders caused by lack of functional proteins that result in a blockage of the corresponding metabolic pathway essential for cellular life. IEM are rare or even very rare conditions, whereas with a collective incidence comprised from 1:800 to 1:2,500 live births. Approximately half of all IEM can be treated biochemically, although the success of such treatment is variable. IEM (especially in the neonatal age) may have a rapid evolution to severe and irreversible neurological and mental deficits, coma, and death. Early diagnosis, allowing presymptomatic treatment, can ameliorate prognosis, prevent severe permanent sequelae, and in certain cases avoid death. To ensure accurate diagnosis, effective treatment, and appropriate follow-up, preventive medicine have implemented for IEM screening programs as a powerful tool of secondary prevention. In this respect, expanded newborn screening programs have increased dramatically in the past decade although the number of diseases included in the screening panel varies from state to state. As a consequence, some nations screen for only one or two IEM, some others for several more (up to a few dozen IEM) leading to an inequality of preventive measures in such as delicate fields. Criteria to support and include screening for a specific condition in each country stand from legislation, financial costs prevalence of the disease in that country, availability of treatments, and dedicated funding sources. Currently, lack of sound and complete evidence, as well as different interpretations of the best evidence available, could also be among the factors contributing to the different screening panels across diverse countries worldwide. Within this view, the recommendable approach to assess current newborn screening programs should be based on the methodologies of health technology assessment, taking into account health economics evidence and ethics applied to well-being policies.
Keywords: expanded newborn screening; inborn errors of metabolism; rare diseases; prevention